Basic Life Support Training On Ability And Self- Confidence Student In Handling Cardiac Arrest - Cahyadi, Faisal Ahmad; Hastuti, Apriyani; Indari, Indari; Kurniawan, Ardhiles Wahyu; Laksono, Bayu Budi; Jamil, Mokhtar; ristanto, riki; Fani, Rif'atul; Roesardhyati, Ratna; Soares, Domingos (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Basic life support or BLS is a series of first aid measures in emergency situations to save the life of someone experiencing cardiac arrest or respiratory problems. Objective This research aims to determine the effect of BLS (basic life support) training on students' knowledge and self-confidence in handling cardiac arrest in students Bachelor of Nursing Study Program ITSK RS Dr Soepraoen Malang. Method In this study, a pre-experimental research design was used, namely research in which before the research was carried out, the sample was given first in the form of a pre-test on December 18th 2024 and at the end of the study the sample was given a post-test on December 22 2024. The population in this study were college study in Department of Nursing with 160 students involving 160 students as samples using the Cluster sampling method. The independent variable in this research is Basic Life Support (BLS) training and the dependent is knowledge and self-confidence, the data from the examination results are analyzed using univariate and bivariate analysis. Results The research results showed that students' knowledge in handling cardiac arrest was mostly poor, as many as 128 students (80%). and after students took part in the training, there was an increase in students, namely to 44 people (27.50%) who answered correctly and those who answered with less marks decreased to 66 students (41.25%). Meanwhile, the level of self-confidence of students in handling cardiac arrest was found to be mostly good, 112 people (70%). Students' self-confidence also increased for the better, to 138 people (86.25%) who answered good and the remaining 22 people (13.75%) answered enough. Conclusion There is an influence of basic life support training on students' level of knowledge and self-confidence in handling cardiac arrest. It is hoped that students can apply the knowledge they have gained from BLS training and continue to increase their knowledge and self-confidence to help victims with cardiac arrest.